Adrenal Insufficiency in Children With Nephrotic Syndrome on Corticosteroid Treatment - Abu Bakar, Karmila; Khalil, Khairunnisa; Lim, Yam Ngo; Yap, Yok Chin; Appadurai, Mirunalini; Sidhu, Sangeet; Lai, Chee Sing; Anuar Zaini, Azriyanti; Samingan, Nurshadia; Jalaludin, Muhammad Yazid (Frontiers in Pediatrics, 2020)
Background: Adrenal insufficiency can result from impaired functions at all levels of hypothalamic-pituitary-adrenal (HPA) axis. We here studied risk factors associated with adrenal insufficiency in children receiving prolonged exogenous steroid treatment for nephrotic syndrome. Method: We performed low-dose Synacthen tests (LDSTs, 0.5 μg/m2) in children with steroid-sensitive nephrotic syndrome four to six weeks after discontinuation of the corticosteroid therapy. We measured early morning serum cortisol levels at baseline and at intervals of 10, 20, 30, and 60 minutes following the stimulation test. We defined normal HPA axis stimulation responses as those with peak cortisol cutoff values >550 nmol/L. Result: We enrolled 37 children for this study research. All children enrolled had normal early morning cortisol levels. However, 13 (35.1%) demonstrated HPA axis suppression (by LDST) four to six weeks after discontinuation of oral prednisolone. Nephrotic syndrome diagnosed before five years of age (OR, 0.75; 95% CI, 0.57–0.99; p = 0.043), and steroid-dependence (OR, 5.58; 95% confidence interval [CI], 1.06–29.34; p = 0.042) were associated with increased risk of developing adrenal suppression after steroid discontinuation. Conclusion: HPA axis suppression may go unnoticed without proper screening. A normal early morning cortisol level (275–555 nmol/L) does not exclude adrenal insufficiency in children with steroid-sensitive nephrotic syndrome. Further screening with LDSTs, particularly in children younger than five years at diagnosis, may be warranted.